Current Status of Endovascular Devices to Treat Abdominal Aortic Aneurysms. (January 2013) - Eckroth-Bernard, Kamell; Garvin, Robert; Ryer, Evan
The introduction of endovascular abdominal aortic aneurysm (AAA) repair has revolutionized the therapeutic approach to patients with AAA. Due to an ongoing and prolific collaboration between vascular interventionalists and biomedical engineers, the devices used to perform endovascular AAA repair have also changed dramatically. The purpose of this publication is to provide an overview of the currently available and upcoming options for endovascular AAA repair.